Antigonus II Gonatas : a political biography - Gabbert, Janice J., 1940- (Routledge, 1997)
Janice J. Gabbert portrays the eventful life of this enigmatic king in a lively and engaging manner. Her aim is to trace the political career of a man about whose life almost no official records survive.